Severity of Hyponatremia and its Influence on Various Complications of Decompensated Chronic Liver Disease - Muhammad Affan Qaiser, Muhammad Asif Baig, Imran Ali Syed, Syed Hammad Wajid Talha Shah, Nazish Butt, Farah Najmi, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective The study quantified the occurrence and intensity of hyponatremia in decompensated chronic liver disease patients Study design: Descriptive Cross sectional study Place and Duration: Department of Gastroenterology, Centre for Liver Diseases, Holy Family Hospital (CLD, HFH) for a total 6 months duration Methodology: Patients aged 13-75 years, both male and female presenting with Clinical, biochemical, and Ultrasonographic findings of cirrhosis were included in this study. Patients' ages, genders, levels of serum hyponatremia, rates of complications, Child-Pugh scores, and other contextual data were recorded in a standardized proforma. The tests were conducted in the hospital's lab, and a pathologist looked over the results. Results: Among 120 study cases, 72 (60 %) patients were male and 48 (40 %) were female patients. The mean age was 50.83 ± 10.50 years; ranging from 30 years to 70 years. Of these 120 study cases, 32 (26.7 %) were from rural areas while 88 (73.3 %) were from urban areas, 35 (29.2%) were poor, 69 (57.5%) were middle income and 16 (13.3%) were having rich socioeconomic status. Child-Pugh class B was noted in 77 (64.2 %) and Child-Pugh class C was noted in 43 (35.8%) of our study cases. The mean serum sodium level was 131.25 ± 4.34 mmol/L ranging from 118 mmol/L to 141 mmol/L and hyponatremia was noted in 64 (53.3%) of our study cases. Mild hyponatremia was noted in 12 (10%), moderate hyponatremia in 28 (23.3%) and severe hyponatremia in 24 (20%) of our study cases. Hepatic encephalopathy was noted in 16 (13.3%), spontaneous bacterial peritonitis in 36 (30%), variceal bleeding in 44 (36.7%) and Hepatorenal syndrome in 24 (20%). Conclusion: Our study found that people with liver cirrhosis were more likely to be hyponatremic than those without the condition. Hyponatremia was associated with being older age, having problems, and being labelled as a Child-Pugh class C. It was also revealed that the number of problems was strongly correlated with the degree to which the hyponatremia had progressed. Nurses, doctors, and anybody else providing care for cirrhotic patients should all keep a close check on their patients' sodium levels. Keywords: Hyponatremia, liver cirrhosis, Serum Sodium, Child-Pugh